2017
DOI: 10.1016/j.msea.2016.10.069
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior of post-processed Inconel 718 manufactured through the electron beam melting process

Abstract: The electron beam melting (EBM) process was used to fabricate Inconel 718. The microstructure and tensile properties were characterized in both the as-fabricated and post-processed state transverse (T-orientation) and longitudinal (L-orientation) to the build direction. Post-processing involved both a hot isostatic pressing (HIP) and solution treatment and aging (STA) to homogenize the microstructure.In the as-fabricated state, EBM Inconel 718 exhibits a spatially dependent microstructure that is a function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(51 citation statements)
references
References 40 publications
5
44
1
1
Order By: Relevance
“…In their subsequent paper [75], anisotropic tensile properties were reported as due to the local agglomerate of porosities rather than the intrinsic properties. The anisotropic tensile properties were further confirmed by Kirka et al [77,186]: both the tensile strength and elongation are higher tested along the building direction that tested perpendicular to the building direction in the as-manufactured sample, and these anisotropic properties almost disappear after post heat-treatment. The microstructure gradient along the building direction was first reported by Unocic et al [187], and was attributed to the height-dependant thermal exposure experienced by different parts of the component [61].…”
Section: Ebm In718mentioning
confidence: 52%
“…In their subsequent paper [75], anisotropic tensile properties were reported as due to the local agglomerate of porosities rather than the intrinsic properties. The anisotropic tensile properties were further confirmed by Kirka et al [77,186]: both the tensile strength and elongation are higher tested along the building direction that tested perpendicular to the building direction in the as-manufactured sample, and these anisotropic properties almost disappear after post heat-treatment. The microstructure gradient along the building direction was first reported by Unocic et al [187], and was attributed to the height-dependant thermal exposure experienced by different parts of the component [61].…”
Section: Ebm In718mentioning
confidence: 52%
“…In instances where the material exhibits crystallographic anisotropy, the resulting columnar-grained material exhibits anisotropic mechanical properties similar to directionally solidified nickel-base (Ni-base) superalloys. 2 As a result, having the means of controlling texture formation in AM materials in a manner to allow either equiaxed or columnar grains as needed based upon the application of the material is beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…After optimal heat treatment, the volume fraction of these two phases is 15-17 vol.% [15], the volume fraction of γ'' being three to four times larger than that of γ' [16]. After an ageing or a heat treatment, between 650°C and 950°C, δ-Ni 3 Nb phases, the [28,30,35]. Rao et al [40] found that HIP followed by AMS 5662 H T had a beneficial effect on the mechanical properties of AM-produced 718 alloys.…”
Section: Microstructure Of In 718 Alloys Produced By Additive Manufacmentioning
confidence: 99%
“…Thus, AM materials present columnar grains parallel to the build direction in LBM [24,25] and EBM processes both [26,27]. The thermal gradient induces epitaxial solidification leading to fine columnar grain architecture and dendrite epitaxial growth inside those grains, both structures are found parallel to the beam direction [28,29]. The formation of dendrites causes the segregation of alloy elements, such as niobium or titanium along interdendritic regions [30].…”
Section: High Temperature Oxidation Of the In 718 Alloymentioning
confidence: 99%